2021
DOI: 10.1162/jocn_a_01663
|View full text |Cite
|
Sign up to set email alerts
|

EEG-based Identification of Evidence Accumulation Stages in Decision-Making

Abstract: Dating back to the 19th century, the discovery of processing stages has been of great interest to researchers in cognitive science. The goal of this paper is to demonstrate the validity of a recently developed method, hidden semi-Markov model multivariate pattern analysis (HsMM-MVPA), for discovering stages directly from EEG data, in contrast to classical reaction-time-based methods. To test the validity of stages discovered with the HsMM-MVPA method, we applied it to two relatively simple tasks where the inte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 84 publications
1
21
0
1
Order By: Relevance
“…Second, in a previous study in which we experimentally manipulated decision difficulty, we saw a very similar bump-stage-bump pattern (Berberyan et al, 2021). In that study, the onset bump of the decision stage showed strong frontal negativity, and the end of the decision stage strong central-parietal positivity -highly resemblant of the current bump topologies of bumps 4 and 5.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Second, in a previous study in which we experimentally manipulated decision difficulty, we saw a very similar bump-stage-bump pattern (Berberyan et al, 2021). In that study, the onset bump of the decision stage showed strong frontal negativity, and the end of the decision stage strong central-parietal positivity -highly resemblant of the current bump topologies of bumps 4 and 5.…”
Section: Discussionsupporting
confidence: 55%
“…This HsMM-MVPA method has been successfully applied to a range of cognitive tasks including associative memory recognition, arithmetic retrieval, and classical short-term memory tasks (Anderson et al, 2018(Anderson et al, , 2016Portoles, Borst, & van Vugt, 2018;van Maanen, Portoles, & Borst, in press;Walsh et al, 2017;Zhang, Borst, Kass, & Anderson, 2017;Zhang, van Vugt, Borst, & Anderson, 2018;Zhang, Walsh, et al, 2018). In a recent validation study, it was found that HsMM-MVPA allows for zooming into processes identified with RT-based methods by finding a range of corresponding cognitive stages (Berberyan, van Maanen, van Rijn, & Borst, 2021).…”
Section: 1lexical Decision Taskmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, we found direct support for this assumption: we did two identical experiments, except that a decision rule was made more difficult in the second experiment. Here, we observed that the decision difficulty had a very clear effect on the duration of one of the stages (Berberyan et al 2021). This also indicated that stages are typically serial, even though the HsMM-MVPA does not enforce this.…”
Section: Limitationsmentioning
confidence: 71%
“…We found that the duration of the penultimate stage was longer for the more difficult decision rule. Consequently the final stage was "pushed backwards" (Berberyan et al 2021), indicating that the onset of the final stage was triggered by an event in the penultimate stage, suggesting serial dependence.…”
Section: Methods Overviewmentioning
confidence: 99%